In situ prey selection of mixotrophic and heterotrophic flagellates in Antarctic oligotrophic lakes: an analysis of the digestive vacuole content - Gerea, Marina; Queimaliños, Claudia; Schiaffino, M. Romina; Izaguirre, Irina; Forn, Irene; Massana, Ramon; Unrein, Fernando (Journal of Plankton Research, 2012)
We investigated the selective predation of mixotrophic and heterotrophic flagellates (MF and HF) on different heterotrophic prokaryote phylotypes (HPP; Bacteria + Archaea ) living in natural assemblages from oligotrophic Antarctic lakes. In situ prey preference was analyzed for the first time on different mixotrophic taxa ( Pseudopedinella sp., Ochromonas -like cells, Chrysophyceae >5 µm). The relative abundances of seven different HPP hybridized by CARD-FISH (catalyzed reporter deposition-fluorescent in situ hybridization) in natural community were compared with the proportions of hybridized cells inside digestive vacuoles. Our results showed some general trends to selectivity over some HPP. Alphaproteobacteria and Betaproteobacteria were the most abundant groups, and strikingly, a negative selection trend was detected in most samples by all bacterivorous protists. In contrast, for Actinobacteria a positive selection trend was observed in most samples, whereas Bacteroidetes seemed to be randomly preyed upon. Interestingly, similar prey preferences were observed in all bacterivorous flagellates. Our results suggest that phylogenetic affiliation determines part of the process of prey selection by protists in these lakes. Nevertheless, other features, such as cell size, morphology and the presence of the S-layer, might also significantly contribute to prey selectivity on the HPP.